A modified gradient-based backpropagation training method for neural networks - Xuewen Mu; Yaling Zhang (2009 IEEE International Conference on Granular Computing, 2009)
A improved gradient-based backpropagation training method is proposed for neural networks in this paper. Based on the Barzilai and Borwein steplength update and some technique of Resilient Propagation method, we adapt the new learning rate to improves the speed and the success rate. Experimental results show that the proposed method has considerably improved convergence speed, and for the chosen test problems, outperforms other well-known training methods.